2014
DOI: 10.4103/0973-1482.131365
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer Effects of CME-1, a Novel Polysaccharide, Purified from the Mycelia of Cordyceps sinensis against B16-F10 Melanoma Cells

Abstract: These results indicate that CME-1 inhibited MMP-1 expressions in B16F10 melanoma cells through either NF-kB or ERK/p38 MAPK down regulation thereby inhibiting B16F10 cell migration. Therefore, we proposed that CME-1 might be developed as a therapeutic potential candidate for the treatment of cancer metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 36 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Several previous studies have shown that the Cordyceps species have anti-cancer activity ( Park et al ., 2009 ; Jayakumar et al ., 2014 ). It has been found that the aqueous extract of Cordyceps militaris (AECM) induces apoptosis of MDA-MB-231 cells by activation of caspases ( Jin et al ., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have shown that the Cordyceps species have anti-cancer activity ( Park et al ., 2009 ; Jayakumar et al ., 2014 ). It has been found that the aqueous extract of Cordyceps militaris (AECM) induces apoptosis of MDA-MB-231 cells by activation of caspases ( Jin et al ., 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that Cordyceps have anti-metastatic, immune-modulatory, antioxidant, anti-inflammatory, insecticidal, antimicrobial, hypolipidemic, hypoglycemic, anti-ageing, and neuro-protective effects ( Ng and Wang, 2005 ; Yue et al ., 2013 ; Lee et al ., 2014 ). Furthermore, this mushroom has been considered as a promising source for anti-cancer drugs due to the anti-metastatic effect against various cancers ( Ng and Wang, 2005 ; Holliday and Cleaver, 2008 ; Zhou et al ., 2009 ; Jayakumar et al ., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…O. sinensis is traditionally used[ 56 57 ] as antidiabetic,[ 58 59 60 61 62 ] antiinflammatory,[ 49 54 63 ] antimicrobial,[ 64 65 ] antioxidant,[ 66 67 68 ] and antitumor agent;[ 44 69 70 71 ] against hypocholesterolemia;[ 72 73 ] and for immunomodulatory properties. [ 74 75 ] It is also used for treatment in several diseases such as cardiovascular,[ 76 77 78 79 ] gastrointestinal,[ 80 ] hepatic,[ 81 82 83 ] neuromuscular,[ 84 85 ] renal,[ 59 85 86 ] and respiratory diseases.…”
Section: Traditional Usesmentioning
confidence: 99%
“…Systemic studies have found that Cordyceps species have numerous biological activities including anti-metastatic, anti-oxidative, anti-inf lammatory, antimicrobial, anti-aging, insecticidal, hypolipidemic, hypoglycemic, and neuroprotective effects. Furthermore, Cordyceps has been considered a promising drug for treating cancer due to its antiproliferative effect [ 1 2 3 4 ].…”
Section: Introductionmentioning
confidence: 99%